2020
DOI: 10.1109/tgrs.2019.2961772
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Lateral Wave for the Interlayer Debonding Detecting in an Asphalt Airport Pavement Using a Multistatic GPR System

Abstract: In this paper, we focus on the detection of the interlayer debonding of the asphalt airport pavement by the Groundpenetrating Radar (GPR) system. Since the interlayer debonding usually occurs in the shallow region of the asphalt airport pavement (several centimeters), it is difficult to interpret the anomalies or the defects from the GPR signals composed of many waves under the boundary conditions. Moreover, the wavelength of the ordinary GPR system is over several centimeters. Therefore, the spatial resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Approximate formulas were generated by HED buried in a four-layered media using generalized reflection coefficients [17] presented by Lu et al, which indicated that the trapped surface wave and the lateral wave propagate along the air-dielectric boundary and between two dielectric layers. Recently, Zou used lateral wave in a four-layered model for interlayer debonding detection in asphalt airport pavement [18]. The problem addressed in this paper parallels the analysis carried out in published work on the EM field of the horizontal electric dipole (HED) [19].…”
Section: Introductionmentioning
confidence: 82%
“…Approximate formulas were generated by HED buried in a four-layered media using generalized reflection coefficients [17] presented by Lu et al, which indicated that the trapped surface wave and the lateral wave propagate along the air-dielectric boundary and between two dielectric layers. Recently, Zou used lateral wave in a four-layered model for interlayer debonding detection in asphalt airport pavement [18]. The problem addressed in this paper parallels the analysis carried out in published work on the EM field of the horizontal electric dipole (HED) [19].…”
Section: Introductionmentioning
confidence: 82%
“…The early detection of debonding is therefore crucial for pavement assessment. The application of GPR in the detection of debonding is usually combined with FWD analysis [75,85], with consistent results validating each other. In addition, the analysis of the GPR signal frequency indicates that the spectrum is sensitive to the structural condition of the pavement, correlating the results with the standardized deflection tests [47] in roads: when comparing damaged zones with undamaged zones, the spectrum bandwidth reduces while the amplitude and the central frequency decreases.…”
Section: Damage Assessment: Debondingmentioning
confidence: 92%
“…GPR is also used to evaluate the quality of grouting treatments [78] applied to stabilize damaged pavements. GPR is also used in the assessment of the asphalt layers' interfaces to detect debonding [75,85]. Other studies were focused on the analysis of airports under special conditions: (i) in the case of airports built over the sea, in order to detect the contact between the filled layers and the natural soil under the sea [86]; and (ii) in the study of airports in frozen areas, in order to detect the depth to the permafrost layer [87].…”
Section: Airportsmentioning
confidence: 99%
See 2 more Smart Citations